Proceedings of BioNLP 15 2015
DOI: 10.18653/v1/w15-3816
|View full text |Cite
|
Sign up to set email alerts
|

Translating Electronic Health Record Notes from English to Spanish: A Preliminary Study

Abstract: The Centers for Medicare & Medicaid Services Incentive Programs promote meaningful use of electronic health records (EHRs), which, among many benefits, allow patients to receive electronic copies of their EHRs and thereby empower them to take a more active role in their health. In the United States, however, 17% population is Hispanic, of which 50% has limited English language skills. To help this population take advantage of their EHRs, we are developing English-Spanish machine translation (MT) systems for EH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…However, it was shown to be of little help to render medical record content more comprehensible to patients [ 155 ]. A systematic evaluation of machine translation tools showed that off-the-shelf tools were outperformed by customized systems [ 156 ]; however, this was not confirmed when using a smaller in-domain corpus [ 157 ]. Encouragingly, medical speech translation was shown to be feasible in a real clinical setting, if the system focused on narrowly-defined patient-clinician interactions [ 158 ].…”
Section: Main Textmentioning
confidence: 99%
“…However, it was shown to be of little help to render medical record content more comprehensible to patients [ 155 ]. A systematic evaluation of machine translation tools showed that off-the-shelf tools were outperformed by customized systems [ 156 ]; however, this was not confirmed when using a smaller in-domain corpus [ 157 ]. Encouragingly, medical speech translation was shown to be feasible in a real clinical setting, if the system focused on narrowly-defined patient-clinician interactions [ 158 ].…”
Section: Main Textmentioning
confidence: 99%
“…development dataset for natural language understanding task without evaluating the quality of the paraphrases. Such general-purpose machine translation systems lack the ability to capture the domain-specific nuances of biomedicine (Liu and Cai, 2015). This suggests the need for a question paraphrasing dataset targeted toward clinical domain.…”
Section: Clinical Text Paraphrasingmentioning
confidence: 99%
“…Also, existing datasets for clinical paraphrasing consist of either short phrases (Hasan et al, 2016) or webpage title texts (Adduru et al, 2018), both of which are not suitable to build a paraphrase generator for QA. One can resort to using external tools such as Google Translate for generating question paraphrases (Neuraz et al, 2018), but these general-purpose tools are not tailored to the medical domain (Liu and Cai, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of NoteAidspa 11 ;s1, W. Liu and Cai (2015) used BLEU score and a bilingual human expert to evaluate three systems: NoteAidspanish, Google Translate, and Bing Translator when translating electronic health records. BLEU is a method for automatic evaluation of machine translation quality (Papineni, Roukos, Ward, & Zhu, 2002).…”
Section: Noteaidspa11ishmentioning
confidence: 99%